The impact of big data analytics capabilities on the innovative capacity of South African organisations : the mediating role of dynamic capabilities - Myres, Hugh (University of Pretoria, 2025)
Mini Dissertation (MPhil (Corporate Strategy))--University of Pretoria, 2024.